Post coronavirus-disease-vaccination immune reconstitution inflammatory syndrome in tuberculosis treatment: a case report - Aadit Mehta; Alok Pant (Journal of Medical Case Reports)
Abstract Background Tuberculosis immune reconstitution inflammatory syndrome is an uncommon condition caused by excessive immune response against Mycobacterium tuberculosis. We report on a case which may have been precipitated by coronavirus disease messenger ribonucleic acid vaccine booster. Case presentation A 47-year old Indian man developed reactivation tuberculosis in the cervical lymph nodes in the setting of immune suppression caused by tumor necrosis factor inhibitor adalimumab. The symptoms improved with starting antituberculous therapy, but 5 days after receiving a coronavirus disease booster messenger ribonucleic acid vaccine, he had recurrence of severe constitutional symptoms. After a detailed evaluation, he was diagnosed with immune reconstitution inflammatory syndrome and was successfully treated with high-dose steroid therapy, which was weaned off over several weeks. Conclusion Immune reconstitution inflammatory syndrome should be considered as a differential in patients who develop paradoxical worsening of symptoms with antitubercular therapy in the setting of immune reconstitution. Hyperactive immune response after infection or messenger ribonucleic acid vaccine booster may have contributed to the development of immune reconstitution inflammatory syndrome syndrome in this patient.